Pengaruh Kepemimpinan Terhadap Kinerja Karyawan Melalui Motivasi Kerja dan Kepuasan Kerja Pada PT. Griya Kenari Properti Di Makassar - Harneisa Syafri; Baso Amang; Masdar Mas’ud (Departement of Mathematics Education, 2023)
This research was conducted with the aim of knowing and analyzing the influence of leadership on employee performance through work motivation and job satisfaction at PT. Griya Kenari Property in Makassar. This research was conducted at PT. Griya Kenari Properti in Makassar, lasts for approximately 2 (two) months, from January to February 2021. The population for this study is all employees at PT. Griya Kenari Properti in Makassar has 55 employees. By using a saturated sampling technique, the sample used is the entire population, namely 55 people. Data collection techniques were carried out through observation, questionnaires and documentation, while data analysis used path analysis. The results showed that the performance of employees at PT. Griya Kenari Properti can be improved by having leadership and work motivation. The direct influence in this study which shows a major contribution is work motivation on employee performance, that with the motivation given, employees will also remain enthusiastic at work and increase their performance so that the company will also achieve company goals. The new finding in this study is that the mediating variable of work motivation plays a major role in mediating leadership on employee performance, with the result that the coefficient of the direct influence of leadership on employee performance becomes larger when it involves work motivation as an intervening variable in the form of an indirect effect. So that the existence of work motivation variables as intervening variables strengthens the influence of leadership on employee performance at PT. Griya Kenari Property.